Analysis of Parental Attitudes Regarding Fish Consumption Patterns on the Nutritional Status of Preschool Children - Nugrahani, Cantika Iva; Christiana, Elisa; Ferdina, Cucun Setya; Himawati, Ernia Haris (LPPM Universitas Prima Nusantara Bukittinggi, 2024)
Background: Providing fish during the golden age is also the best strategy to overcome the problem of stunting in IndonesiaPurpose : The aim of this research is to analyze parents' attitudes regarding fish consumption patterns on nutritional status of preschool children.Methods: This research is a quantitative study that uses a cross-sectional study design. The population in this study were all students and parents/guardians at Kindergarten Al-Badriyah Sampang. The sample in this study used a total sample of 214 samples.Results: The research results show that the significance value is 0.000 <0.05, so there is a significant relationship, with a power level of 1.00 meaning the strength of the correlation is very strong, and the relationship value is positive (0.542 ).Conclusion: There is a significant relationship between parents' attitudes regarding fish consumption patterns and the nutritional status of preschool children